Regionalmanagement als Motor für eine nachhaltige Raumentwicklung? - Kistenmacher, Hans; Mangels, Kirsten (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
This article is based on a research study into the evaluation of regional management in the rural county of Rottal-Inn, which serves as a starting point for a discussion on the potential offered by regional management to “accelerate” sustainable spatial development. It begins with a critical analysis of the principles and postulates of the vision of sustainable spatial development and of the current state of implementation of this vision in Germany, in particular with regard to more comprehensive spatial planning. The article then goes on to focus in turn on the origins, content and organisation of regional management in Rottal-Inn, as well as on its effectiveness with regard to projects it has been applied to and its managerial efficiency; this in turn leads into a discussion of the contribution of process- and implementation-orientated regional management to sustainable spatial development. Departing from the view occasionally encountered which might be expressed as “Regional planning is dead — long live regional management”, the authors conclude by drawing some conclusions regarding area-specific regional management and its links to regional planning.
Keywords: Article